함재기 이·착함 시뮬레이션 시스템 개발 및 활용 - 이한진(Han Jin Lee); 홍사영(Sa Young Hong); 김용환(Yong Hwan Kim); 유원선(Won-Sun Ruy); 박광필(Kwang Phil Park); 김승균(Seungkeun Kim); 신현욱(Hyunwook Shin) (大韓造船學會 論文集, 2024)
The Republic of Korea Navy is reviewing the development of a ship capable of operating STOVL (Short Take-Off and Vertical Landing) aircraft. However, the Navy has no experience in operating or building such ships, so engineering means are needed to review the design and confirm the operating concept at the concept and basic design stages. In this paper, the authors introduce the results of developing a STOVL aircraft take-off and landing simulation system that reflects the ship's seaworthiness characteristics and major design dimensions based on engineering-based modeling and simulation technology in response to the Navy's needs. The simulation system was developed in which the engineering characteristics of the ship were estimated based on the basic design, and the motion characteristics of the aircraft were implemented by developing equations of motion for a general STOVL. The system was developed to simulate naval aircraft's take-off and landing process and deck movement situation and to confirm the ship operation scenario. By using this simulation system, the Navy will be able to examine not only the ship's structural characteristics at the basic design stage but also the basic conditions for special operational requirements such as take-off and landing.